2015
DOI: 10.1016/j.tube.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 gene region polymorphisms and susceptibility to tuberculosis in Vietnam

Abstract: Summary Humans exposed to Mycobacterium tuberculosis (Mtb) show variation in susceptibility to infection and differences in tuberculosis (TB) disease outcome. Toll-like receptor 9 (TLR9) is a pattern recognition receptor that mediates recognition of Mtb and modulates Mtb-specific T-cell responses. Using a case-population design, we evaluated whether single nucleotide polymorphisms (SNPs) in the TLR9 gene region are associated with susceptibility to pulmonary or meningeal TB as well as neurologic presentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…TLR3, 7, 8 and 9 depend on the protein Unc-93 homolog B1 (UNC93B1) to traffic from the endoplasmic reticulum to endolysosomal compartments where they detect nucleic acids [ 10 , 11 ]. TLR9 has previously been shown to recognize mycobacterial DNA [ 12 , 13 ]. TLR7 and TLR8 recognize single-stranded RNA and RNA degradation products from viruses and bacteria, and polymorphisms in TLR7 and 8 have been associated with increased susceptibility to pulmonary tuberculosis [ 11 , 14 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…TLR3, 7, 8 and 9 depend on the protein Unc-93 homolog B1 (UNC93B1) to traffic from the endoplasmic reticulum to endolysosomal compartments where they detect nucleic acids [ 10 , 11 ]. TLR9 has previously been shown to recognize mycobacterial DNA [ 12 , 13 ]. TLR7 and TLR8 recognize single-stranded RNA and RNA degradation products from viruses and bacteria, and polymorphisms in TLR7 and 8 have been associated with increased susceptibility to pulmonary tuberculosis [ 11 , 14 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mutations and polymorphisms within the genes involved in the TLR pathway have been associated with susceptibility to infection in TB. A recent study of patients with TBM in Vietnam was the first to demonstrate an association between single nucleotide polymorphisms (SNPs) in the TLR9 gene region and TBM . Further, a Vietnamese study found an association between TLR2 SNP T597C and the development of TBM and miliary TB, suggesting that TLR2 influences the dissemination of M.tb .…”
Section: Pathogenic and Pathophysiologic Mechanisms Within The Brain mentioning
confidence: 99%
“…Like pulmonary tuberculosis 25 , 26 , variety of host factors including, genetic makeup, antigenic exposure, initial innate immune responses and the ensuing adaptive immune responses may determine the clinical outcomes in IOTB. Polymorphisms in TLR genes 27 30 , IL-10 26 and defective TLR9 responses have been reported to increase susceptibility to pulmonary tuberculosis 15 . However, there is lacuna in knowledge about the immune responses in pathogenesis of IOTB.…”
Section: Discussionmentioning
confidence: 99%